2002
DOI: 10.1614/0043-1745(2002)050[0120:aaceog]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and cost effectiveness of GPS-assisted wild oat mapping in spring cereal crops

Abstract: Managing weed infestations in a spatially precise manner requires accurate and cost-effective weed identification techniques. The goal of our research was to quantify the accuracy of continuous weed presence–absence maps and assess how management based on those maps may affect producer net returns. Each continuous sampled map covered the entire field and contained vector polygons labeled as either wild oat presence or wild oat absence. The accuracy of the continuous wild oat maps at each sampling time was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…In that study, application of half doses of herbicides was the most profitable strategy in sites with yields above 5000 kg ha −1 , whereas no spraying could be the best option in sites with yields of below 3500 kg ha −1 . A similar conclusion has been reached in studies conducted in other semi‐arid areas (Van Wychen et al. , 2002), challenging the usefulness of high‐cost herbicides under low‐yield conditions.…”
Section: Discussionsupporting
confidence: 81%
“…In that study, application of half doses of herbicides was the most profitable strategy in sites with yields above 5000 kg ha −1 , whereas no spraying could be the best option in sites with yields of below 3500 kg ha −1 . A similar conclusion has been reached in studies conducted in other semi‐arid areas (Van Wychen et al. , 2002), challenging the usefulness of high‐cost herbicides under low‐yield conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Scoring panicle density from a combine proved to be a reliable and relatively inexpensive method (9€ ha −1 ) to monitor A. sterilis abundance and to plan herbicide use. Prices charged commercially in Montana for continuous A. fatua mapping at harvest are very similar to our figures (Van Wychen et al. , 2002).…”
Section: Discussionsupporting
confidence: 80%
“…Because of the uncertainty associated with all these factors, the addition of buffer areas around the georeferenced weed patches has been used in various studies (Rew et al. , 1996; Van Wychen et al. , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in this study have several important implications for SSWM of S. halepense . Previous studies have shown that the economic feasibility of using SSWM systems is conditioned by the frequency of re‐mapping (Van Wychen et al. , 2002; Barroso et al.…”
Section: Discussionmentioning
confidence: 99%